Fracking in Deutschland: Eine Option für die Zukunft! - Kai A. Konrad; Ronnie Schöb (Wirtschaftsdienst, 2014)
Deutschland hat nicht unerhebliche Mengen an unkonventionellen Erdgasreserven, die in tiefen Lagen in Schiefergestein gebunden sind. Die Diskussion um die Frage, ob diese beachtlichen Reserven durch moderne Bohr- und Fördertechniken (sogenanntes Hydraulic Fracturing (Fracking)) gehoben werden sollten, spitzt sich derzeit zu. Die Autoren nutzen die Theorie erschöpfbarer Ressourcen, Erkenntnisse zur globalen Klimaerwärmung und die Investitionstheorie und sprechen sich dafür aus, mit der Extraktion abzuwarten. – – Extraction of shale gas in Germany (fracking) is better left as an option for the future. Today, owners of deposits in many other countries have uncertain property rights and extract too quickly. German deposits may appreciate in value if left in the ground. They also better contribute to national energy security there than if extracted and depleted. Waiting also allows Germany to learn from the mistakes of others and to take this new information and the improvements in extraction technology into account when deciding about extraction in the future. Such decisions should not be left to the resource extraction industries. Their objectives are likely to differ from the objective of maximising the rent from the nation's shale gas.
Keywords: O32; O38; Q35; Q38; 330; Erdgasgewinnung; Naturstein; Klimawandel; Volkswirtschaftliche Investitionstheorie; Erschöpfbare Ressourcen; Deutschland